Effect of human skin explants on the neurite growth of the PC12 cell line. Issue 3 (12th March 2013) - Lebonvallet, Nicolas; Pennec, Jean‐Pierre; Le, Christelle; Pereira, Ulysse; Boulais, Nicholas; Cheret, Jeremy; Jeanmaire, Christine; Danoux, Louis; Pauly, Gilles; Misery, Laurent
Abstract The skin is a densely innervated organ. After a traumatic injury, such as an amputation, burn or skin graft, nerve growth and the recovery of sensitivity take a long time and are often incomplete. The roles played by growth factors and the process of neuronal growth are crucial. We developed an in vitro model of human skin explants co‐cultured with a rat pheochromocytoma cell line differentiated in neuron in presence of nerve growth factor (NGF). This model allowed the study of the influence of skin explants on nerve cells and nerve fibre growth, probably through mediators produced by the explant, in a simplified manner. The neurite length of differentiated PC12 cells co‐cultured with skin explants increased after 6 days. These observations demonstrated the influence of trophic factors produced by skin explants on PC12 cells.